Marine alien species in Italy: A contribution to the implementation of descriptor D2 of the marine strategy framework directive - SERVELLO, GIANNA; ANDALORO, FRANCO; AZZURRO, ERNESTO; CASTRIOTA, LUCA; CATRA, MARCELLO; CHIARORE, ANTONIA; CROCETTA, FABIO; D’ALESSANDRO, MICHELA; DENITTO, FRANCESCO; FROGLIA, CARLO; GRAVILI, CINZIA; LANGER, MARTIN R.; et al. (Mediterranean Marine Science, 2019)
The re-examination of marine alien species or Non-indigenous species (NIS) reported in Italian Seas by December 2018, is here provided, particularly focusing on establishment success, year of first record, origin, potential invasiveness, and likely pathways. Furthermore, their distribution is assessed according to marine subregions outlined by the European Union (EU) Marine Strategy Framework Directive: Adriatic Sea (ADRIA), Ionian Sea and Central Mediterranean Sea (CMED), and Western Mediterranean Sea (WMED). In Italy, 265 NIS have been detected with the highest number of species being recorded in the CMED (154 species) and the WMED (151 species), followed by the ADRIA (143). Most of these species were recorded in more than one subregion. The NIS that have established stable populations in Italian Seas are 180 (68%), among which 26 have exhibited invasive traits. Among taxa involved, Macrophyta rank first with 65 taxa. Fifty-five of them are established in at least one subregion, mostly in the ADRIA and the CMED. Crustacea rank second with 48 taxa, followed by Polychaeta with 43 taxa, Mollusca with 29 taxa, and Pisces with 28 taxa, which were mainly reported from the CMED. In the period 2012-2017, 44 new alien species were recorded, resulting in approximately one new entry every two months. Approximately half of the NIS (~52%) recorded in Italy have most likely arrived through the transport-stowaway pathway related to shipping traffic (~28% as biofoulers, ~22% in ballast waters, and ~2% as hitchhikers). The second most common pathway is the unaided movement with currents (~19%), followed by the transport-contaminant on farmed shellfishes pathway (~18%). Unaided is the most common pathway for alien Fisshes, especially in CMED. Escapes from confinement account for ~3% and release in nature for ~2% of the NIS. The present NIS distribution hotspots for new introductions were defined on the first recipient area/location in Italy. In ADRIA the hotspot is Venice which accounts for the highest number of alien taxa introduced in Italy, with 50 newly recorded taxa. In the CMED, hotspots of introduction are the Taranto and Catania Gulfs, hosting 21 first records each. The Strait of Sicily represents a crossroad between the alien taxa from the Atlantic Ocean and the Indo-Pacific area. In the WMED, hotspots of bioinvasions include the Gulfs of Naples, Genoa and Livorno. This review can serve as an updated baseline for future coordination and harmonization of monitoring initiatives under international, EU and regional policies, for the compilation of new data from established monitoring programs, and for rapid assessment surveys.